The use of egocentric and allocentric reference frames in static and dynamic conditions in humans - Moraresku, Sofiia; Vlček, Kamil (Physiological research, 2020)
The dissociation between egocentric and allocentric reference frames is well established. Spatial coding relative to oneself has been associated with a brain network distinct from spatial coding using a cognitive map independently of the actual position. These differences were, however, revealed by a variety of tasks from both static conditions, using a series of images, and dynamic conditions, using movements through space. We aimed to clarify how these paradigms correspond to each other concerning the neural correlates of the use of egocentric and allocentric reference frames. We review here studies of allocentric and egocentric judgments used in static two- and three-dimensional tasks and compare their results with the findings from spatial navigation studies. We argue that neural correlates of allocentric coding in static conditions but using complex three-dimensional scenes and involving spatial memory of participants resemble those in spatial navigation studies, while allocentric representations in two-dimensional tasks are connected with other perceptual and attentional processes. In contrast, the brain networks associated with the egocentric reference frame in static two-dimensional and three-dimensional tasks and spatial navigation tasks are, with some limitations, more similar. Our review demonstrates the heterogeneity of experimental designs focused on spatial reference frames. At the same time, it indicates similarities in brain activation during reference frame use despite this heterogeneity.
Keywords: neuropsychologické testy; mapování mozku; prostorová paměť; pozornost; zraková percepce; Judgment; Photic Stimulation; Attention; lidé; světelná stimulace; vnímání prostoru; Brain Mapping; Visual Perception; mínění; Spatial Memory; Humans; Space Perception; Neuropsychological Tests